In Vivo Antitumor, Pharmacological and Toxicological Study of Pyrimido[ 4′,5′:4,5] thieno(2,3-b)quinoline with 9-hydroxy-4-(3-diethylaminopropylamino) and 8-methoxy-4-(3-diethylaminopropylamino) Substitutions - Kiran Kumar, Hulihalli N.; Rohit Kumar, Heggodu G.; Khandagale, Ajay S.; Advirao, Gopal M. (Anti-Cancer Agents in Medicinal Chemistry, 2021)
Background: We previously synthesized two DNA intercalative Pyrimido[4’,5’:4,5]thieno(2,3-b) quinolines (PTQ), 9-hydroxy-4-(3-diethylaminopropylamino)pyrimido[4’,5’:4,5]thieno(2,3-b) quinolines (Hydroxy- DPTQ) and 8-methoxy-4-(3-diethylaminopropylamino) pyrimido[4’,5’:4,5]thieno(2,3-b) quinolines (Methoxy-DPTQ), and reported their cytotoxicity against cancer cell lines. Methods: In the present study, we sought to analyze the antitumor activity of Hydroxy-DPTQ and Methoxy-DPTQ on Ehrlich’s ascites carcinoma in vivo models, along with other pharmacological activities and toxicity. Results: In this study, both the test molecules studied possess potent in vivo antitumor activity without any hematological, biochemical or nephrotoxicity. Significant tumor regression was observed after treatment with both the test molecules, which is suggested by the decrease in the bodyweight of tumour-bearing mice. Mean survival time of mice with tumor was increased from 16 days to 25 and 29 days after 40 and 80 mg/kg Hydroxy- DPTQ treatment, respectively, with a similar result for Methoxy-DPTQ. A dose-dependent increase in lifespan up to 80-85% was also displayed by both Hydroxy-DPTQ and Methoxy-DPTQ. Reduction in the tumor volume of mice, upon treatment with molecules also confirmed their antitumor activity. These molecules also exhibited pharmacological activities such as antioxidant, anti-inflammatory and analgesic activities. Administration of Hydroxy-DPTQ and Methoxy-DPTQ not only reduced the level of lipid peroxidation in tumor bearing mice but also restored the superoxide dismutase, glutathione, and catalase levels to normal, substantiating the antioxidant property. Also, treatment of Hydroxy-DPTQ and Methoxy-DPTQ inhibited the pain to approximately 60-80% and 19-33%, respectively. Further, the treatment with Hydroxy-DPTQ and Methoxy-DPTQ reversed the abnormality in the RBC, WBC and haemoglobin levels, and gentamicin induced nephrotoxicity. Conclusion: Hydroxy-DPTQ and Methoxy-DPTQ are good antitumor molecules with pharmacological properties.
Keywords: 3- b)quinolines